2002
DOI: 10.1128/aac.46.11.3418-3421.2002
|View full text |Cite
|
Sign up to set email alerts
|

gyrA and gyrB Mutations Are Implicated in Cross-Resistance to Ciprofloxacin and Moxifloxacin in Clostridium difficile

Abstract: A total of 198 nonrepetitive clinical strains of Clostridium difficile isolated from different French hospitals in 1991 (n ‫؍‬ 100) and 1997 (n ‫؍‬ 98) were screened for decreased susceptibility to fluoroquinolones by plating onto Wilkins-Chalgren agar containing 16 g of ciprofloxacin per ml. The frequency of decreased susceptibility was 7% (14 of 198) and was identical for the years 1991 and 1997. Serogroups C, H, D, A9, and K accounted for five, four, two, one, and one of the resistant strains, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 26 publications
3
96
1
1
Order By: Relevance
“…In C. difficile, as in many other bacterial species, resistance is determined by amino acid substitutions in the quinolone resistance-determining region (QRDR) of the target enzymes (27). Since this bacterium does not have genes for topoisomerase IV, these alterations are located in the QRDR of either GyrA or GyrB, the DNA gyrase subunits (11,34). Recent studies indicated that the replacement of Thr82 with Ile in GyrA characterized 93% of European toxigenic C. difficile isolates resistant to fluoroquinolones, including the hypervirulent epidemic clone 027/NAP1/III (12,34).…”
mentioning
confidence: 99%
“…In C. difficile, as in many other bacterial species, resistance is determined by amino acid substitutions in the quinolone resistance-determining region (QRDR) of the target enzymes (27). Since this bacterium does not have genes for topoisomerase IV, these alterations are located in the QRDR of either GyrA or GyrB, the DNA gyrase subunits (11,34). Recent studies indicated that the replacement of Thr82 with Ile in GyrA characterized 93% of European toxigenic C. difficile isolates resistant to fluoroquinolones, including the hypervirulent epidemic clone 027/NAP1/III (12,34).…”
mentioning
confidence: 99%
“…The QRDRs of gyrB (nucleotides 1059-1448) and gyrA (nucleotides 71-460) were amplified by PCR as described previously [6]. To investigate the entire gyrBA region, beyond the defined QRDR, primers flanking the entire ORFs of gyrB and gyrA were designed.…”
Section: Pcr Amplification and Sequencing Of The Qrdr And Gyrba Open mentioning
confidence: 99%
“…In C. difficile, resistance is linked to a homoplasic Thr82Ile substitution in the quinolone resistance-determining region (QRDR) of the GyrA DNA gyrase subunit, a hallmark of globally disseminated 027/BI/NAP1 strains [5]. Several additional mutations that map to the QRDR of gyrA and gyrB have also been reported in C. difficile, whereas the type IV topoisomerase is absent in C. difficile as well as several other pathogenic species [6]. Molecular characterisation of fluoroquinolone resistance in C. difficile also suggests the existence of undetermined mechanisms among resistant strains lacking QRDR mutations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance of C. difficile to tetracycline varies in different countries, ranging from 2.4 to 41.67% [32]. Fry et al reported that although the tetracycline resistance gene tetM is predominant in C. difficile, others such as tetW are found in human and animal strains [33].…”
Section: Resistancementioning
confidence: 99%
“…Alterations in the quinolone-resistance determining region (QRDR), which confers resistance to fluoroquinolones, have been identified in C. difficile [32]. Resistance of C. difficile to tetracycline varies in different countries, ranging from 2.4 to 41.67% [32].…”
Section: Resistancementioning
confidence: 99%